Adherence of Candida albicans to Five Long‐Term Silicone‐Based Denture Lining Materials Bonded to CAD‐CAM Denture Base. Issue 4 (16th June 2022) - Tasopoulos, Theodoros; Vrioni, Georgia; Naka, Olga; Diamantatou, Theodora; Zoidis, Panagiotis; Tsakris, Athanasios
Abstract: Purpose: Knowledge about quantifying the number as well as the retention and adhesion of Candida albicans blastoconidia to silicone denture liners is limited. Thus, the aim of this in vitro study was to explore the adherence of C. albicans to the surface of five long‐term silicone‐based soft denture lining materials, using artificial saliva. Materials and methods: A total of 50 specimens (10 × 10 × 3 mm) of five long‐term resilient liners (Molloplast‐B; GC Reline Soft; Elite Soft Relining; Tokuyama Sofreliner S; Ufigel SC), bonded to a computer‐aided design and computer‐aided manufacturing denture base, were prepared. The specimens were inoculated and incubated in artificial saliva for 1 and 24 hours with a standardized (2.8 × 10 6 cfu/ml) C. albicans suspension. At the end of the incubation period, the specimens were stained with acridine orange and observed using fluorescence microscopy. Results: After 1 hour and in 24 hours, Molloplast B demonstrated significantly earlier adherence of C. albicans cells compared to the other chairside materials ( p < 0.001 and p < 0.001, respectively), where the mean number of cells also increased in the frontal parts. Regarding the rate of C. albicans proliferation from 1 to 24 hours within the materials, there was an increase in all materials (Molloplast B: p < 0.001; GC Reline Soft: p = 0.220; Elite Soft Relining: p = 0.032; Tokuyama Sofreliner S: p = 0.001; Ufigel Sc: p = 0.001). The Ufigel Sc showed a significant 2.5‐fold increase at 24 hours. Conclusions: Long‐term silicone denture liners accumulate a significant amount of C. albicans blastoconidia and their coverage by them increases progressively over time.